2018
DOI: 10.1136/bmjopen-2017-018745
|View full text |Cite
|
Sign up to set email alerts
|

Are risk factors for preterm and early-term live singleton birth the same? A population-based study in France

Abstract: ObjectivesTo investigate whether risk factors for preterm (<37 weeks gestation) and early-term birth (37 and 38 weeks gestation) are similar.DesignNationally representative cross-sectional study of births.SettingFrance in 2010.ParticipantsLive singleton births (n=14 326).Primary and secondary outcome measuresPreterm and early-term birth rates overall and by mode of delivery (spontaneous and indicated). Risk factors were maternal sociodemographic characteristics, previous preterm birth, height, prepregnancy bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
29
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 52 publications
11
29
2
1
Order By: Relevance
“…These suggest that there could be shared mechanisms, with some differences. In spontaneous deliveries, diabetes mellitus was a strong determinant of late preterm and early term birth (aOR > 2), as well polyhydramnios, oligohydramnios, placental ischemia, other hypoxia [39], and a previous preterm birth [39,43]. Infection and inflammation, on the other hand, were risk factors for spontaneous preterm but not early term birth [39].…”
Section: Etiology and Pregnancy Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These suggest that there could be shared mechanisms, with some differences. In spontaneous deliveries, diabetes mellitus was a strong determinant of late preterm and early term birth (aOR > 2), as well polyhydramnios, oligohydramnios, placental ischemia, other hypoxia [39], and a previous preterm birth [39,43]. Infection and inflammation, on the other hand, were risk factors for spontaneous preterm but not early term birth [39].…”
Section: Etiology and Pregnancy Complicationsmentioning
confidence: 99%
“…The most recent US findings relate national income inequality to preterm birth time trends [48]. Research on associations of sociodemographic risk factors with early term birth are lacking, but a French study found many similar determinants including short stature, a low level of education, and foreign origin (for other European and Sub-Saharan nationals), although the impact of risk factors was greater for preterm than for early term births [43]. Primiparity was a risk factor for preterm birth, but not early term birth [43], as also found by Brown et al in Canada [39,42].…”
Section: Population Determinants: Socio-demographic Lifestyle and Enmentioning
confidence: 99%
See 1 more Smart Citation
“…The study methods have been published previously [20,21]. Briefly, this study is based on data from the National Health Insurance Research (NHIR) database provided by the Taiwan National Health Research Institute.…”
Section: Data Sourcementioning
confidence: 99%
“…hypertension), as well as obstetric complications (e.G. placenta abruptio) during the pregnancy period [21,24].…”
Section: Definitionmentioning
confidence: 99%